Model Pembelajaran VAK (Visualization, Auditory, Kinestethic) untuk Meningkatkan Prestasi Belajar Mata Kuliah Telaah Kurikulum Mahasiswa Pendidikan Biologi 2012 - Lilik Mawartiningsih (Universitas Sebelas Maret, 2016)
Do research on learning model VAK (Visualization, Auditory, Kinestethic) on Assessing curriculum subjects. This study aims to 1). To determine students' achievement in the subject class of 2012 Assessing curriculum as applied learning model VAK (Visualization , Auditory , Kinestethic), 2). To determine the response or responses of students to study with the model VAK (Visualization, Auditory, Kinestethic). This research was conducted at the University of PGRI Ronggolawe (UNIROW) Tuban on the School Year 2015/2016 odd semester. This study uses a pre experimental design, where the object of the study was the 7th semester student of class 2012 who took a course curriculum Assessing many as 20 students. Instruments in this study 1). Test, test given to students to obtain data on student achievement, 2). Questionnaire, for students regarding the response or responses to learning that uses the model VAK (Visualization, Auditory, Kinestethic). Student achievement can be calculated by the value obtained by the students. Values obtained for individual students, where students who attend learning if the student earned a minimum of B. In addition calculated too classical learning success. For the analysis of data on student response to the learning model VAK (Visualization, Auditory, Kinestethic) descriptive quantitative look at the answers of students to the aspects in question, is then calculated by the presentation of the results showed that students who obtained A = 15%, AB = 30%, B = 40%, BC = 15%. And the success of classical learning 85%. The response of students to study with the model VAK (Visualization, Auditory, Kinestethic) is positive, proved to be> 70% of the students were delighted.Keywords: VAK Learning, Ahcievement Study, Course Curriculum